2002
DOI: 10.2307/3072011
|View full text |Cite
|
Sign up to set email alerts
|

Soil Microbial Responses to Herbivory in an Arctic Tundra Heath at Two Levels of Nutrient Availability

Abstract: We tested the hypothesis that herbivory accelerates nutrient cycling through nutrient-rich soils and decelerates nutrient cycling through nutrient-poor soils in a welldrained arctic tundra heath by measuring effects of herbivory on soil and plant properties in control areas and areas treated with NPK fertilizer. The impact of herbivores was studied with two types of exclosures, one excluding reindeer and the other excluding both rodents and reindeer. We predicted that herbivores would enhance soil microbial pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
40
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 42 publications
2
40
0
Order By: Relevance
“…These mechanisms occur simultaneously and can have contrasting effects on soil nutrient availability and hence primary production. For instance, empirical studies have found positive (Hobbs and others 1991;Frank and Evans 1997;McNaughton and others 1997), negative (Pastor and others 1993;Ritchie and others 1998;Fornara and Du Toit 2008) or mixed effects (Olofsson and others 2001;Olofsson and Oksanen 2002;Stark and Grellmann 2002;Stark and others 2003) of herbivores on nitrogen (N) cycling and primary production.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These mechanisms occur simultaneously and can have contrasting effects on soil nutrient availability and hence primary production. For instance, empirical studies have found positive (Hobbs and others 1991;Frank and Evans 1997;McNaughton and others 1997), negative (Pastor and others 1993;Ritchie and others 1998;Fornara and Du Toit 2008) or mixed effects (Olofsson and others 2001;Olofsson and Oksanen 2002;Stark and Grellmann 2002;Stark and others 2003) of herbivores on nitrogen (N) cycling and primary production.…”
Section: Introductionmentioning
confidence: 99%
“…For two reasons this is a suitable system to test the effects of herbivory on nutrient availability across a productivity gradient: (1) plant community structure and stoichiometry is known to vary dramatically along topographic gradients at relatively small spatial scales (Bjö rk and others 2007; Chu and Grogan 2010; Sundqvist and others 2011a), and (2) reindeer have been shown to have strong but varying effects on nutrient availability (Olofsson and others 2001;Stark and Grellmann 2002;Stark and others 2002;Olofsson and others 2004;Van der Wal and Brooker 2004;Stark and others 2010). So far, studies on the effects of reindeer on nutrient availability have focused primarily on N, likely because it is considered to be the main limiting nutrient in tundra ecosystems (Shaver and Chapin 1980;Tamm 1991;Aerts and Chapin 2000).…”
Section: Introductionmentioning
confidence: 99%
“…In arctic communities, intensive mammalian herbivory on aboveground plant parts has been reported to result in either acceleration (Stark and Grellmann 2002) or deceleration (Olofsson and Oksanen 2002) of nutrient cycling rates. Whether herbivory accelerates or decelerates nutrient cycling may be crucial to the recovery of ecosystems after herbivore infestation.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on the impact of reindeer on Fennoscandian arctic-alpine nature have improved our knowledge on the impact of reindeer on the coverage of lichens (Johansen et al, 1995;Ihse & Allard, 1995;Johansen & Karlsen, 1996;Allard et al, 1998), on nutrient mineralization rate and primary production (Stark et al, 2000;Olofsson et al, 2001;Stark & Grellmann, 2002), on ground temperatures (Olofsson et al, 2003) and on abundances of ground-dwelling (Suominen et al, 1999a;Suominen et al, 1999b) and galling (Olofsson & Strengbom, 2000;Herder et al, 2004) invertebrates. Vegetation studies have corroborated the predictions of IDH in the context of lichen rich heathlands, which become overwhelmingly dominated by Cladina stellaris in the absence of reindeer, whereas only crustose lichens survive on the most grazed and trampled sites along reindeer fences.…”
Section: Introductionmentioning
confidence: 99%